Antiproliferative, antimicrobial and antioxidant properties of Cedrus libani and Pinus pinea wood oils and Juniperus excelsa berry oil. (4th March 2022) - Venditti, A.; Maggi, F.; Saab, A. M.; Bramucci, M.; Quassinti, L.; Petrelli, D.; Vitali, L. A.; Lupidi, G.; El Samrani, A.; Borgatti, M.; Bernardi, F.; Gambari, R.; et al.
Abstract: In this paper we report the analysis of essential oils from the woods of C. libani and P. pinea and from the berries of J. excelsa . Several differences were observed with respect to previous studies. In particular, the wood of C. libani was mainly characterized by sesquiterpenes with himachalenes isomers, ( E )- and ( Z )-α-atlantones and α-acorenol (7.0%) as most representative compounds; in P. pinea wood oil and J. excelsa berries oil were observed differences mainly among the minor components with different isomers of some specific compounds not previously recognized. The oils were assessed in selected bioactivity tests. C. libani wood oil resulted the most active in both the antioxidant and cytotoxic (against human A375 malignant melanoma, human MDA-MB 231 breast adenocarcinoma and human HCT116 colon carcinoma cell lines) tests; on the other hand in the antimicrobial assay it was observed a different susceptibility of different bacteria to the different oils. All the oils exerted a remarkable activity against the yeast Candida albicans . Taken together, these results support some of the traditional uses of these three plants in the Mediterranean area and give evidence of their potential on an industrial level.